Effects of comprehensive therapy based on traditional Chinese medicine patterns in stable chronic obstructive pulmonary disease: a four-center, open-label, randomized, controlled study - Li Su-yun; Li Jian-sheng; Wang Ming-hang; Xie Yang; Yu Xue-qing; Sun Zi-kai; Ma Li-jun; Zhang Wei; Zhang Hai-long; Cao Fan; Pan Ying-chao (BMC, 2012)
Abstract Background Traditional Chinese medicine (TCM) has been used to treat chronic obstructive pulmonary disease (COPD) for many years. This study aimed to evaluate the efficacy and safety of the comprehensive therapy based on the three common TCM patterns in stable COPD patients. Methods A four-center, open-label randomized controlled method was conducted. A total of 352 patients were divided into the trial group (n = 176, treated with conventional Western medicine and Bu-Fei Jian-Pi granules, Bu-Fei Yi-Shen granules, and Yi-Qi Zi-Shen granules based on the TCM patterns respectively) and the control group (n = 176, treated with conventional Western medicine). The frequency and duration of acute exacerbation, lung function, clinical symptoms, 6-minute walking distance (6MWD), dyspnea scale and quality of life were observed during a 6-month treatment period and at a further 12-month follow-up. Results A total of 306 patients completed the study fully. The full analysis set (FAS) population was 350 and the per-protocol analysis set (PPS) population was 306. After the 6-month treatment and 12-month follow-up, there were significant differences between the trial and control group in the following: frequency of acute exacerbation (FAS: P = 0.000; PPS: P = 0.000); duration of acute exacerbation (FAS: P = 0.000; PPS: P = 0.001); FEV1 (FAS: P = 0.007; PPS: P = 0.008); symptoms (FAS: P = 0.001; PPS: P = 0.001); 6MWD (FAS: P = 0.045; PPS: P = 0.042); dyspnea scale (FAS: P = 0.002; PPS: P = 0.004); and physical domain (FAS: P = 0.000; PPS: P = 0.000), psychological domain (FAS: P = 0.008; PPS: P = 0.011), social domain (FAS: P = 0.001; PPS: P = 0.000) and environment domain (FAS: P = 0.015; PPS: P = 0.009) of the WHOQOL-BREF questionnaire. There were no differences between the trial and control group in FVC, FEV1% and adverse events. Conclusions Based on the TCM patterns, Bu-Fei Jian-Pi granules, Bu-Fei Yi-Shen granules and Yi-Qi Zi-Shen granules have beneficial effects on measured outcomes in stable COPD patients over the 6-month treatment and 12-month follow-up, with no relevant between-group differences in adverse events. Trial Registration This trial was registered at Chinese Clinical Trial Register Center, ChiCTR-TRC-11001406.